The Role of Socio-Cultural Factors in Teaching Students a Minority Language - E. V. Voevoda; G. N. Mutaf (Высшее образование в России)
The article addresses the problems concerned with teaching minority languages in the regions of Russia and the Gagauz Autonomy in the Republic of Moldova. The authors analyze sociocultural factors exerting motivating and demotivating influence on the use of regional languages. The results of a survey conducted in Komrat State University have shown that the Gagauz language does not fully cater to the social, intellectual and personal needs of the younger generation. Along with that, the socio-cultural component of university curricula serves as a motivating factor, promotes interest in learning a minority language and contributes to building linguo-cultural and national identity.